Teaching Through Texts and Pictures. A Contribution of Jan Amos Comenius to Education - María Esther Aguirre Lora (Universidad Autónoma de Baja California, 2001)
This article deals with some of the traditions which produced the first illustrated book with didactic purposes. This book is Orbis sensualium pictus or The Visible World in Pictures, by the Moravian thinker John Amos Comenius (Uhersky Brod, 1592 - Amsterdam, 1670). The debates, stirred up by Renaissance scholars' dissatisfaction with the schools' deficiencies and shortcomings, had become increasingly widespread and sharp since then. Particularly in the case of Comenius' work, the argument was over problems in the teaching of Latin, which the author tried to correct through a pleasant treatment of the subject. He used the students' mother tongue to introduce Latin, thus making the language understandable for the pupils, as well as rendering it favorable to the acquisition of encyclopedic contents, in the word's broadest sense. The book integrates illustrations and texts in Latin and in the vernacular for each theme. Together, these constitute authentic pictures of the 17th Century.